The Prevalence of Renal Failure: Results From the German Health Interview and Examination Survey for Adults, 2008–2011 (DEGS1) - Girndt, Matthias (Dtsch Arztebl Int, 2016)
BACKGROUND: The prevalence of non–end stage renal failure among adults in Germany is unknown. Accurate figures would enable us to estimate the overall need for kidney replacement therapies and the unexploited potential for disease prevention. Renal failure is also an important cardiovascular risk factor. Until now, American prevalence figures have often been applied to Germany despite dissimilarities between the two populations. METHODS: We analyzed data on renal function from the nationwide German Health Interview and Examination Survey for Adults, 2008–2011 (DEGS1), which was carried out by the Robert Koch Institute. The glomerular filtration rate was estimated (eGFR) from the serum creatinine and cystatin C levels (CKD-EPI formula) and a semiquantitative measure of albuminuria. Relationships between renal failure and its possible determinants were quantified with adjusted prevalence ratios (PR) and 95% confidence intervals (95% CI). RESULTS: Roughly 2.3% (95% CI: [1.9; 2.6]) of persons aged 18–79 had an eGFR below 60 mL/min/1.73 m(2). The prevalence rose with age. We extrapolated these figures conservatively to persons aged 80 and above, who were not included in the DEGS1, and arrived at a figure of at least 2 million persons in Germany with renal failure. 11.5% of the population have albuminuria of at least 30 mg/L. Diabetes mellitus (PR = 2.25, 95% CI: [1.59; 3.16]) and arterial hypertension (PR = 3.46, 95% CI: [1.95; 6.12]) are important determinants. CONCLUSION: This study provides the first representative estimate of the prevalence of renal failure in Germany. The condition is highly dependent on age but less prevalent than previously assumed on the basis of American prevalence figures.